2016
DOI: 10.1103/physrevlett.116.156402
|View full text |Cite
|
Sign up to set email alerts
|

Unified Theory ofPTandCPInvariant Topological Metals and Nodal Superconductors

Abstract: As PT and CP symmetries are fundamental in physics, we establish a unified topological theory of PT and CP invariant metals and nodal superconductors, based on the mathematically rigorous KO theory. Representative models are constructed for all nontrivial topological cases in dimensions d=1, 2, and 3, with their exotic physical meanings being elucidated in detail. Intriguingly, it is found that the topological charges of Fermi surfaces in the bulk determine an exotic direction-dependent distribution of topolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
192
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(197 citation statements)
references
References 59 publications
4
192
0
Order By: Relevance
“…The fully gapped topological phases have been classified in terms of the existence of various antiunitary symmetriese.g., time-reversal and particle-hole symmetries [4,5]-and also the importance of the unitary symmetries is understood [6][7][8][9][10][11][12]. Recently there have been attempts to classify also the gapless topological phases [13][14][15][16][17][18][19][20]. In an ordinary d-dimensional metal a d − 1-dimensional Fermi surface separates the filled and empty states.…”
Section: Introductionmentioning
confidence: 99%
“…The fully gapped topological phases have been classified in terms of the existence of various antiunitary symmetriese.g., time-reversal and particle-hole symmetries [4,5]-and also the importance of the unitary symmetries is understood [6][7][8][9][10][11][12]. Recently there have been attempts to classify also the gapless topological phases [13][14][15][16][17][18][19][20]. In an ordinary d-dimensional metal a d − 1-dimensional Fermi surface separates the filled and empty states.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that Fermi surfaces of Hamiltonians with CP symmetry squaring to +1 can possess a non-trivial Z 2 charge, making them topologically stable against CP -preserving perturbations [32,33]. We now express the invariant in terms of the Pfaffian P (k).…”
mentioning
confidence: 99%
“…This interpretation naturally follows from the picture presented here. That Fermi surfaces may be topologically stable features of a gap structure follows from a topological Z 2 invariant associated with nodes of codimension-1 in even-parity time-reversal symmetry-broken superconductors [61,64]. Additional Bogoliubov Fermi surfaces generically occur on the Fermi surface equator, i.e., in the vicinity k z ¼ 0, of even-parity chiral pairings with odd M. For odd M, jJ; Mi is odd under twofold rotation about the z axis.…”
Section: Pseudospin-singlet Hamiltonian From Symmetrymentioning
confidence: 99%
“…Pseudospin-triplet pairing must be of odd-parity type, and therefore, nodes of codimension-1 (i.e., surfaces) are not topologically stable [61,64]. Since chiral pairing states are generically spin selective, the effective pseudopsin splitting δ is nonzero, implying that point nodes on the rotation axis (if they exist) are nondegenerate.…”
Section: Pseudospin-triplet Hamiltonian From Symmetrymentioning
confidence: 99%